Perception of Strategy Formulation Process in the Sport Environment and Its Influence on Performance of the Sport Club - Tripes, Stanislav (2018)
The purpose of this study is to address how NPSO managers perceive the steps of the strategy formulation process, managerial approaches, and skills within the strategic planning process and how these perceptions impact organisational performance. The number of non-profit sports organisations (NPSOs) associated under selected national sports governing bodies in the Czech Republic is almost 8,000. The explanatory sequential mixed methods design was used where the quantitative phase was based on an in-depth questionnaire distributed to NPSOs. The questionnaire covers the perception of the whole strategic planning process and was answered by 351 NPSOs. The quantitative data was clustered and later used as a sampling tool for the qualitative phase and 11 managers were selected for a semi-structured interview. The results of both phases supported the theory that the strategy and strategic planning process in NPSOs are not conducted explicitly although some steps in the process are non-systematically used. The strategy, as presented in mainstream sports management literature, is not useful for an NPSO. The recommendation for managers is to use the stakeholder approach for strategy formulation and implementation, where managers work actively with their stakeholders. The strategy perception analysis in the sports environment was not provided and the discussion of strategy in NPSOs is lacking. This dissertation uncovers a new field of research.